Pengaruh derajat keasaman (pH) dalam proses presipitasi hidroksida selektif ion logam dari larutan ekstrak spent catalyst - Kevin Cleary Wanta1; Federick Dwi Putra; Ratna Frida Susanti; Gelar Panji Gemilar; Widi Astuti; Shinta Virdhian; Himawan Tri Bayu Murti Petrus (Jurnal Rekayasa Proses, 2019)
Nickel hydroxide [Ni(OH)2] is an important compound in producing rechargeable batteries. The synthesis of Ni(OH)2 can be carried out using a hydroxide precipitation method from a solution containing nickel (II) (Ni2+) ions. In this study, the synthesis of Ni(OH)2 was investigated from the solution of extracted spent catalyst using sulfuric acid (H2SO4) solution. The selective precipitation was conducted using sodium hydroxide (NaOH) solution and the degree of acidity (pH) was varied in the range of 4–14. The operating temperature was kept constant at 30oC. The experimental results showed that the optimum precipitation conditions of Al3+ and Ni2+ ions were obtained at different pH where the optimum pH values were 6 and 10, respectively. Precipitate samples were characterized and the results showed that the purity of Ni(OH)2 in those samples was 13.1%. The XRD results indicated that the structure of precipitate still contains other impurities, such as Na2SO4, Al(OH)3 and those compounds were mutually agglomerate.